MUTAGENISITAS PARAKUAT DIKLORIDA PADA SEL SPERMATID MENCIT SWISS-WEBSTER (Mus musculus) DENGAN UJI MIKRONUKLEUS - Cucu Hadiansyah; Siskasari Polianti (BIOTIKA Jurnal Ilmiah Biologi, 2002)
Research on the mutagenicity of paraquat to the spermatid of Swiss-Webster mice had been  studied  by micronucleus assay.  The doses of paraquat, which were  17;  25,5;  34 mg/kg bw, physiological saline as negative control, and 40 mg/kg bw of cyclophosphamide as positive control, each administered intraperitoneally at six consecutive times to male Swiss-Webster mice. The spermatid samples taken 16 days later since the first treatment by cell masseration method in trypsin and DNase solution, to formed  germ cells suspension.  Cells  suspension  were  filtered  (mesh  no. 325) and centrifuged (100 rpm, 5 minutes) then the pellet were smeared and stained by Giemsa staining. The micronucleus in spermatid (MN-spermatid) were observed in these preparation as a dark blue spherical or ellipsoidal node with size among 1/5 – 1/3 to the nucleus diameter and counted per 500 spermatid per animal. The frequencies of MN-spermatid observed after having induced by paraquat was significant (p<0.05) at the dose of 25.5 mg/kg bw and highly significant (p<0.01) at the dose of 34 mg/kg bw to the negative control.  The induction of micronucleus by paraquat had a positive correlation  to  the given doses. On this research, 34 mg/kg bw of paraquat induced 12.0 ± 2.45‰ were similar (p<0.01) to the induction of 40 mg/kg bw of cyclophosphamide (15.6 ± 2.00‰), these indicated that paraquat had a mutagenic effect to the mice spermatid as same as a level of cyclophosphamide mutagenicity.Research on the mutagenicity of paraquat to the spermatid of Swiss-Webster mice had been  studied  by micronucleus assay.  The doses of paraquat, which were  17;  25,5;  34 mg/kg bw, physiological saline as negative control, and 40 mg/kg bw of cyclophosphamide as positive control, each administered intraperitoneally at six consecutive times to male Swiss-Webster mice. The spermatid samples taken 16 days later since the first treatment by cell masseration method in trypsin and DNase solution, to formed  germ cells suspension.  Cells  suspension  were  filtered  (mesh  no. 325) and centrifuged (100 rpm, 5 minutes) then the pellet were smeared and stained by Giemsa staining. The micronucleus in spermatid (MN-spermatid) were observed in these preparation as a dark blue spherical or ellipsoidal node with size among 1/5 – 1/3 to the nucleus diameter and counted per 500 spermatid per animal. The frequencies of MN-spermatid observed after having induced by paraquat was significant (p<0.05) at the dose of 25.5 mg/kg bw and highly significant (p<0.01) at the dose of 34 mg/kg bw to the negative control.  The induction of micronucleus by paraquat had a positive correlation  to  the given doses. On this research, 34 mg/kg bw of paraquat induced 12.0 ± 2.45‰ were similar (p<0.01) to the induction of 40 mg/kg bw of cyclophosphamide (15.6 ± 2.00‰), these indicated that paraquat had a mutagenic effect to the mice spermatid as same as a level of cyclophosphamide mutagenicity.